SENTIMEN INVESTOR DAN EKSPEKTASI PERTUMBUHAN LABA JANGKA PANJANG PADA INDUSTRI NON KEUANGAN DI INDONESIA - Maulina Agustya; Faisal Faisal (Departemen Manajemen, 2018)
This study aims to determine the effect of investor sentiment on long-term growth expectations non financial industry in Indonesia. The population of this study was conducted on listed non financial companies in Indonesia Stock Exchange period 2012-2016. The purposive sampling was used in this study therefore 20 non financial companies taken as sample. The data used are secondary data of annual financial statements including profit and loss report, company performance summary, stock price and composite stock price index in 2012-2016. Regression linear analysis was used to analyze the data collected. The result of the study partially shows that investor sentiment has a significant positive effect on long-term growth expectations. Besides, the result of the study simultaneously shows investor sentiment has a significant positive effect on long-term growth expectations.Keywords: Investor Sentiment, Profit Growth, Theory Behavior Finance, Returns On Asset (ROA), Book Value.